Effects of Biocide Chlorine on Biochemical Responses of the Dinoflagellate Prorocentrum minimum - Ebenezer, Vinitha (Water environment research : a research publication of the Water Environment Federation, 2015)
Effects of the biocide sodium hypochlorite (NaOCl) on the dinoflagellate Prorocentrum minimum were assessed. Growth rate, pigment concentrations, and chlorophyll autofluorescence were monitored up to 72 hours after NaOCl exposure, and these parameters showed dose- and time-dependent decrease. The 72-hour EC₅₀ was 0.983 mg/L. Additionally, enzymatic activities of lipid peroxidation and reduced glutathione were significantly altered with increasing NaOCl and exposure time. Thus, NaOCl at doses of 0.5 mg/L induces physiological and biochemical changes in P. minimum, suggesting that chlorine concentrations observed in power plant discharges and in drinking water systems are potentially detrimental to microalgae